Percutaneous Nephrolithotomy Versus Laparoscopy in the Management of Large Proximal Ureteral Stones: The Experience of Two Different Settings - Mousavi Bahar, Seyed Habibollah; Amirhassani, Shahriar; Nouralizadeh, Akbar; ZerafatJou, Nikan; Rasiuli, Jaber (Urology Journal, 2019)
Purpose: This study was conducted to compare the success rate and complications of percutaneous nephrolithotomy (PCNL) and laparoscopic ureterolithotomy for the treatment of large proximal ureteral stones. Materials and Methods: In this prospective cohort study, the success rate and complications in 52 patients undergoing PCNL in Hamadan’s Shahid Beheshti Hospital and 55 patients undergoing laparoscopic ureterolithotomy in Tehran’s Shahid Labbafinejad Hospital were compared. All patients had large proximal ureteral stones. Results: In the PCNL group, the mean age was 47.78 ±16.72 years, 75% were male, and 50% of calculi were on the upper right side and the rest on upper left side. The mean duration of surgery was 32 ± 9.4 minutes and success rate 100%. The mean stone size was 18.33 ± 2.63 mm in PCNL group and 21.29 ± 2.18 mm in laparoscopy group which was significantly different (P <.001). In the laparoscopy group, the mean age of patients was 42.92 ± 16.10 years and 83.6% were male. In this group, 46.6% of calculi were on the right side and the rest were on the left side. The mean duration of surgery was 107.43 ± 22.86 minutes and success rate was 100%. There was not a statistically significant association between surgical technique and age, gender, stone location, mean hospital stay length after surgery, degree of hydronephrosis and success rate (P >.05). However, surgery duration was significantly shorter in the PCNL group compared to the laparoscopy group (P <.001) and the decrease in hemoglobin, hematocrit and serum urea level was more pronounced in the PCNL group than in the laparoscopy group. Conclusion: PCNL and laparoscopic ureterolithotomy met with the same success rate in the treatment of upper large ureteral stones. However, the two methods should be utilized depending on the hospital facilities and equipment, surgical team qualifications, and patient conditions.